PENGARUH TINGKAT UTANG (LEVERAGE), KEPEMILIKAN MANAJERIAL, DAN PROFITABILITAS TERHADAP PENERAPAN KONSERVATISME AKUNTANSI PADA PERUSAHAAN KONSTRUKSI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2019 - Wahyu Adhi Prawira; Prahasto Ajie Mubarok (Sekolah Pascasarjana Perbanas Jakarta, 2023)
This study aims to determine the effect of debt levels, managerial ownership, and profitability on the application of accounting conservatism. The population in this study were all construction and real estate sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2017-2019 period. Selection of research samples using purposive sampling method with predetermined criteria. Based on these criteria, the sample in this study were 31 companies. The data used are secondary data. This study uses multiple linear regression analysis and hypothesis testing using the t test and the coefficient of determination. Interesting results show that all variables affect accounting conservatism, leverage, managerial ownership and profitability.